Penyuluhan Hukum Perkembangan Informasi Dan Teknologi Serta Dampak Penyalahgunaan Jejaring Sosial Pada Generasi Muda Di Negeri Lesluru Maluku Tengah - Akyuwen, Rory Jeff; Pariela, Marselo Valentino Geovani; Hetharie, Yosia; Wasia, Zacilasi (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: The young generation is a national asset that must be safeguarded, protected, guided and nurtured so that they are not trapped in the negative influence of technological, communication and information developments. Likewise, the younger generation in Lesluru Country, TNS District, Central Maluku Regency, as the successor to Lesluru Country who need education and legal understanding regarding the impact of misuse of social networks due to developments in technology, communication and information.Purposes of the Research: The purpose of writing this article is to provide legal understanding and education to the people of Lesluru State, TNS District, Central Maluku Regency regarding the development of Technology, Communication and Information and the impact of using social networks among the younger generation in Lelsuru Country.Methods: Legal counseling activities in the country of Lesluru are carried out by means of a panel discussion method in which the presenters deliver the material in turns then followed by questions and answers between the speakers and the community.Results / Findings / Novelty of the Research: Social networks that are currently very accessible to the younger generation, including in Lesluru, Central Maluku. This of course not only has a positive impact but often has negative consequences due to the unwise use of social networks. Therefore, as a young generation who will later become the leaders of the nation, even this nation needs to understand well about the wise use of social networks in order to have a positive impact on the younger generation.